2017
DOI: 10.1021/acs.jpcc.7b02941
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Aspects of Particle-Assisted Breath Figures in Polystyrene–Alumina Hybrid Free Standing Film

Abstract: Polystyrene−alumina hybrid free standing films with amino-functionalized breath figure (BF) cavities were fabricated from a suspension of the amino-functionalized amphiphilic-modified alumina particles in polystyrene/chloroform solution by employing a one-step casting process. The role of the film thickness and the particle concentration on the BF microstructural aspects such as the pore size, pore density, amino group surface density, etc. was reported. The dry film thickness increased from 0.91 to 5.6 μm on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Among them, the design of new film‐forming materials or the research on the modification, not only has more important theoretical significance, but has more engineering application value. [ 9,17,18 ] Therefore, it is necessary to present an overall review of the membrane materials on the basis of recent reports. Currently, there are amphiphilic polymers, [ 19,20 ] star‐shaped polymers, [ 10,21,22 ] comb‐shaped polymers, [ 23 ] rod‐ linear copolymers, [ 24,25 ] hyper‐branched polymers, [ 26 ] graft polymers, [ 27 ] organic‐inorganic hybrid polymers, [ 28,29 ] inorganic nanoparticles, [ 30 ] oxidized clusters, [ 31 ] and small molecule compounds [ 32 ] used in the preparation of porous membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the design of new film‐forming materials or the research on the modification, not only has more important theoretical significance, but has more engineering application value. [ 9,17,18 ] Therefore, it is necessary to present an overall review of the membrane materials on the basis of recent reports. Currently, there are amphiphilic polymers, [ 19,20 ] star‐shaped polymers, [ 10,21,22 ] comb‐shaped polymers, [ 23 ] rod‐ linear copolymers, [ 24,25 ] hyper‐branched polymers, [ 26 ] graft polymers, [ 27 ] organic‐inorganic hybrid polymers, [ 28,29 ] inorganic nanoparticles, [ 30 ] oxidized clusters, [ 31 ] and small molecule compounds [ 32 ] used in the preparation of porous membranes.…”
Section: Introductionmentioning
confidence: 99%
“…In this method, uniform water droplets serve as templates via nucleation, growth, and arrangement driven by the evaporation of a volatile solvent . After solidification and further evaporation, exquisite honeycomb-patterned porous films can be prepared and utilized as microreactors, , separation membranes, , cell culture substrates, , superhydrophobic materials, lithography templates, , and others. …”
Section: Introductionmentioning
confidence: 99%
“…Aer the evaporation of water and solvent, the ordered hexagonal lattice comes into being in order to reduce the free energy. 10,11 Aerward, countless important studies have been reported on porous lms including the hole pattern formation mechanism, [12][13][14][15] choice, design and synthesis of polymers, [16][17][18][19][20][21] effect of solvent and substrate, 22,23 environment conditions, 19,21 the reprocessing methods and applications [1][2][3][4][5][6][7][8][24][25][26] and so on. Although the hole pattern formation mechanism is not completely understood at present, this method is known to require precise control over the processing environment conditions, and the polymers used in BFM usually have to be specially designed and synthesized in order to obtain a good quality in pore size and distribution.…”
Section: Introductionmentioning
confidence: 99%